Financial analysis of pond area extension in Pacific white shrimp culture at Cantigi Indramayu - Diatin, Iis; Kusumawardany, U. (Jurnal Akuakultur Indonesia, 2010)
Pacific white shrimp is one of the primadona of fishery commodities. This shrimp is superior as it resists to diseases and also high productivity. Jati Hasil Diri (JHD) located in Cantigi Indramayu is one of the pacific white shrimp culture company. In order to develop the business, this company planned to extent their pond area from 26 to 42 Ha. This plan was therefore needed to be financially analyzed to confirm its feasibility. There were two different scenarios of area extension, first scenario was to extent pond area without any technical improvement, and the second scenario was to extent pond area with technical improvement. The result of the study shows that the pond area extension was feasible with NPV of Rp7.221.427.150,00  and  Rp29.867.006.067,00, the net B/C of  2,62 and 7,7  and  also the  IRR of 47,84%  and 146,55% for the first and second scenario, respectively. Sensitivity analysis indicated that the business is still feasible to be operated at a maximal of feed price the increase of 38,84% for the first scenario and 119,36% for the second scenario or if the shrimp price decrease with a maximum decrease of 18,81% and 41,12% at first and second scenario, respectively. The first business scenario is more sensitive as compare to the second scenario. Key words: Pacific white shrimp, Cantigi Indramayu, pond, technical improvement, sensitivity analysis   ABSTRAK Udang vaname merupakan salah satu komoditas perikanan yang menjadi primadona, karena keunggulannya yaitu tahan terhadap penyakit dan menghasilkan produktivitas yang cukup tinggi. Usaha Jati Hasil Diri (JHD) di Cantigi Indramayu adalah salah satu perusahaan yang bergerak dalam usaha budidaya udang vaname. Dalam rangka mengembangkan usahanya, perusahaan berencana untuk menambah  luas lahan tambaknya dari 26 Ha menjadi 42 Ha. Sehingga perlu dikaji melalui analisis kelayakan finansial, apakah penambahan luas lahan ini layak atau tidak untuk diusahakan. Pengembangan ini menggunakan dua skenario yaitu skenario pertama adalah perluasan lahan   tanpa ada perbaikan teknis dan skenario ke dua adalah   perluasan lahan yang disertai dengan perbaikan teknis. Hasil analisis menunjukkan bahwa pengembangan luas lahan  pada  Usaha JHD layak untuk diusahakan  dengan  nilai NPV  pada skenario 1 dan 2 masing-masing sebesar  Rp7.221.427.150,00 dan  Rp29.867.006.067,00, net B/C sebesar 2,62 dan 7,7 dan IRR sebesar 47,84% dan 146,55%. Analisis sensitivitas menunjukkan bahwa usaha masih layak dijalankan jika terjadi kenaikan harga pakan udang  pada skenario 1 maksimal sebesar 38,84%  dan skenario 2 sebesar 119,36%, sedangkan penurunan harga jual udang  vaname  maksimal pada skenario 1 sebesar 18,81% dan skenario 2 sebesar 41,12%.  Pengembangan usaha pada skenario 1 lebih sensitif dibandingkan skenario 2. Kata kunci: Udang vaname, Cantigi Indramayu, tambak, perbaikan teknis, analisis sensitivitas